Pengaruh Locus of Control Terhadap Moral Disengagement pada Pengurus Organisasi Mahasiswa di UAI - Rahmawati, Siti; Nurfadilah, Nurfadilah; Hadiansyah, Andri; Aditya, Vibby Salsabila (Universitas Al Azhar Indonesia, 2024)
Moral degradation behavior that often occurs in students in general is of particular concern to researchers when they should have an important role as agents of social change in society. This moral degradation behavior describes moral disengagement, namely a person's cognitive mechanism to justify inhumane or morally violating behavior. The purpose of this research is to determine the influence of locus of control on moral disengagement in student organization administrators at Al Azhar University Indonesia. This research uses a quantitative approach with simple linear regression analysis techniques. The subjects in this research were 81 people with the characteristics of being active students who served as administrators in several student organizations at UAI. The research results show that locus of control can be a predictor of moral disengagement in student organization administrators at UAI. The locus of control variable contributes to moral disengagement amounting to 58.9% and the rest is due to other factors.Keywords - Locus of Control, Moral Disengagement, Student Organization Administrators.